2021
DOI: 10.1186/s12877-021-02484-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there gender differences in the trajectories of self-rated health among chinese older adults? an analysis of the Chinese Longitudinal Healthy Longevity Survey (CLHLS)

Abstract: Background Self-rated health (SRH) is a good predictor of morbidity and mortality. Extensive research has shown that females generally report poorer SRH than males but still tend to live longer. Previous studies used cross-sectional or pooled data for their analyses while ignoring the dynamic changes in males’ and females’ SRH statuses over time. Furthermore, longitudinal studies, especially those that focus on older adults, typically suffer from the incompleteness of data. As such, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that self-reported health among older men and women is a valid measure of the objective health status of respondents, a significant predictor of survival in advanced age along with being a powerful predictor of healthy longevity (4,6). The perception of health status varies in different cultures and countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that self-reported health among older men and women is a valid measure of the objective health status of respondents, a significant predictor of survival in advanced age along with being a powerful predictor of healthy longevity (4,6). The perception of health status varies in different cultures and countries.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of inequalities between men and women based on their gender and age indicates that age is considered a more cultural and socio-historical category, being less perceived as a biological and natural process by itself. Gender is regarded as a significant health determinant which additionally shapes the patterns of developing diseases, approach to health protection, and medical treatment availability as well (4). The roots of inequalities in health related to gender are numerous, mutually intertwined, and complex.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sleep duration, sleep quality, and other variables were collected through questionnaires. Although we designed the SRH questionnaire with reference to many large cohort studies ( 6 , 18 , 36 ), and conducted detailed reliability and validity assessments on variables such as sleep duration, sleep quality, and self-rated health, the variable acquisition method was relatively subjective, and the information was not as accurate as the objective evaluation method. We also did not monitor other residual confounding such as sleep duration variability, social jetleg, the number of wake-ups from sleep, fatigue and stress.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study was performed in a medical university in eastern China, from April to September 2021. The questionnaire was designed by experts in the fields of epidemiology, medical statistics, and sociology according to other large-scale cohort studies (6,(16)(17)(18)(19), including basic demographics, sleeping behaviors, other lifestyle factors, biorhythm variables, and health status. We used proportional stratified cluster random sampling method to recruit undergraduates of various majors.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…This study aims to explore the mediating effect of health performance ( Health ) between basic medical insurance and elderly family income inequality. We measure the health performance of the elderly based on the question of “Health status.” Referring to the previous literature ( 40 ), we assign 1 to Health if the elderly answer unhealthy, 2 for fair, and 3 for healthy.…”
Section: Data Variables and Empirical Modelmentioning
confidence: 99%